In data we trust? The implications of datafication for social monitoring - José van Dijck (Matrizes, 2017)
Today there is a remarkable tolerance for Big Brother and Big Business routinely accessing citizens’ personal information also known as Big Data. Part of the explanation for this may be found in the gradual normalization of datafication as a new paradigm in science and society. Datafication is becoming a leading principle, not just amongst techno-adepts, but also amongst scholars. This article deconstructs the ideological grounds of datafication arguing that in many respects datafication is rooted in problematic ontological and epistemological claims. The ideology of dataism shows characteristics of a widespread belief in the objective quantification of human behavior through online media technologies.